2013
DOI: 10.1136/heartjnl-2012-303217
|View full text |Cite
|
Sign up to set email alerts
|

Ankle pressures in UK South Asians with diabetes mellitus: a case control study

Abstract: South Asians with DM had higher ankle pressures versus without and were similar to 10 years older Europeans with DM. Prospective studies on ankle pressures for development of diabetes or cardiovascular disease are warranted in South Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…Diabetic South Asians in the U.K. had significantly higher ankle pressures compared to non-diabetic individuals. 112 In the Chennai Urban Population Study, the prevalence of PAD (ankle-brachial index [ABI] < 0.9) in those with normal glucose tolerance, impaired glucose tolerance and diabetes was 2.7, 2.9 and 6.3% and those with known diabetes had a 7.8% PAD prevalence compared to 3.5% in those newly diagnosed with diabetes. 113 South Asians tend to have more distal PAD which may be due to the higher diabetes prevalence and hence the predilection for smaller vessels.…”
Section: Macrovascular Complications Of Diabetes (Table 2)mentioning
confidence: 99%
See 3 more Smart Citations
“…Diabetic South Asians in the U.K. had significantly higher ankle pressures compared to non-diabetic individuals. 112 In the Chennai Urban Population Study, the prevalence of PAD (ankle-brachial index [ABI] < 0.9) in those with normal glucose tolerance, impaired glucose tolerance and diabetes was 2.7, 2.9 and 6.3% and those with known diabetes had a 7.8% PAD prevalence compared to 3.5% in those newly diagnosed with diabetes. 113 South Asians tend to have more distal PAD which may be due to the higher diabetes prevalence and hence the predilection for smaller vessels.…”
Section: Macrovascular Complications Of Diabetes (Table 2)mentioning
confidence: 99%
“…Diabetic South Asians in the U.K. had ankle pressures that are similar to those of diabetic Europeans who were 10 years older. 112 The Northwest Diabetes Foot Study showed that South Asians were less likely to have PAD compared to Europeans (9% vs 24%) and also had a lower risk of amputation. 116 South Asians were also found to have a lower risk of diabetic foot ulcers compared to Europeans – prevalence 5.5% vs 1.8% which was partly attributed to the lower rate of PAD.…”
Section: Macrovascular Complications Of Diabetes (Table 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…South Asians are more insulin resistant at younger ages at lower BMIs than Europeans 22 . The ankle blood pressure increase with type 2 diabetes is greater in South Asians compared to Europeans 23 . The primary outcome was to study the differences in the associations between the brachial and ankle SBP with BMI and WHtR.…”
Section: Introductionmentioning
confidence: 84%